Study of Rapid Visual Screening of Buildings for High Potential Seismic Hazard According to Indonesian Standard - Wahyuni, Endah; Aji, Pujo; Budi, Firman (IPTEK Journal of Proceedings Series, 2017)
This paper presents a study of Rapid Visual Screening (RVS) using FEMA 154 and applied in Indonesia based on SNI 1726. RVS is a method to asses potential earthquake hazard of a building based on visual observation (â€œsidewalk surveyâ€) of the exterior and interior building if possible, and a Data Collection Form. This study is intended to see how important the RVS of the FEMA 154 can be implemented in Indonesia with a case study at Yogyakarta. The buildings that reviewed were assumed to have the same parameters as mention in FEMA 154 and compatible with SNI 1726 (Indonesian earthquake map). The results from field survey were compared to the numerical analysis. From the case study, it was found that the administration building of ATK Academy, the dormitory building of Ministry of Internal Affairs, the office building of Department of Agriculture, and the educational building of Health Polytechnics have a score more than 2, and the buildings are also declared safe according to SNI 1726.